Usefulness of Acceptability and Feasibility Assessment in Studies of Nursing Interventions - Garizábalo-Dávila, Claudia Milena; Rodríguez-Acelas, Alba Luz; Cañon-Montañez, Wilson (Investigación y Educación en Enfermería, 2023)
Nursing interventions constitute an essential component in the discipline and play a central role in the distinction of the nursing practice with regards to other health professionals. In light of the theory, authors like Burns and Grove, define nursing interventions as deliberate cognitive, physical or verbal activities, which are implemented in individuals and families, seeking therapeutic objectives that contribute to health and wellbeing. In turn, for Sidani and Braden, these are described as treatments, therapies, procedures, or actions developed by health professionals within a specific situation of the patient, for the purpose of modifying current conditions and leading to beneficial health outcomes.